Low temperature annealing effects on the stability of Bi nanowires. Issue 3 (9th November 2015) - Cassinelli, Marco; Romanenko, Anton; Reith, Heiko; Völklein, Friedemann; Sigle, Wilfried; Trautmann, Christina; Toimil‐Molares, Maria Eugenia
Abstract : To investigate the physical properties of Bi nanowires and to explore their possible implementation in thermoelectric devices, it is essential to understand their chemical and thermal stability in air both at room and moderate temperatures. In this work, we study the influence of low temperature annealing processes on the morphology and composition of the wires by scanning and transmission electron microscopy and by Raman spectroscopy, revealing the formation of a metal oxide phase. This oxidation process initiates an increase of the nanowires surface roughness at low annealing temperatures, while clear protuberances are formed at 250 °C. Difficulties to electrically contact single Bi nanowires, as well as the high resistance values measured and reported by other groups, are attributed to this oxidation process, which constitutes a clear challenge for the reliable characterization of Bi nanowires and the investigation of their performance.